A114 SYSTEMATIC REVIEW AND META-ANALYSIS: ENDOSCOPIC AND HISTOLOGIC PLACEBO RATES IN INDUCTION AND MAINTENANCE TRIALS OF ULCERATIVE COLITIS. (1st March 2018) - Ma, C; Guizzetti, L; Panaccione, R; Fedorak, R; Parker, C E; Nguyen, T; Khanna, R; Feagan, B G; Jairath, V
Abstract: Background: Treatment targets in ulcerative colitis (UC) have evolved to include normalization of objective endoscopic and histologic endpoints. Minimizing the endoscopic and histologic placebo response and remission rate is critical for the conduct of efficient randomized controlled trials (RCTs) and development of new treatments, in order to maximize ability to detect differences between active comparator and placebo. Aims: To quantify the endoscopic and histologic placebo response and remission rates in induction and maintenance UC RCTs and to identify trial design factors influencing these rates. Methods: MEDLINE, EMBASE, and the Cochrane Library were searched from inception through March 1, 2017 for placebo-controlled RCTs of adult patients with UC treated with aminosalicylates, immunosuppressants, corticosteroids, biologics, and oral small molecules. Endoscopic and histologic placebo response and remission rates for induction and maintenance trials were pooled using a random-effects model. Patient- and trial-level covariates were evaluated by constructing stratum-specific rates of placebo response/remission and by random-effects meta-regression analysis. Results: Placebo endoscopic response/remission rates were reported in 45 induction and eight maintenance trials; placebo histologic response/remission rates were reported in nine induction trials. Pooled estimates for placebo induction endoscopic remission, induction endoscopic response, and maintenance endoscopic remission rates were 25% [95 confidence interval (CI): 22–30%], 36% [29–43%], and 20% [16–24%], respectively. The pooled histologic remission rate in induction trials was 16% [10–25%]. Disease severity, disease duration, trial setting, trial phase, class of active comparator, trial follow-up duration, and endoscopic sub-score criterion for trial inclusion were not predictive of placebo endoscopic or histologic remission rates. Conclusions: Pooled placebo endoscopic and histologic response and remission rates vary according to whether trials are designed for induction or maintenance. Potential strategies to further reduce these rates include standardization of histologic scoring as well as the definitions used for response and remission. Funding Agencies: None